Factors Associated with Length of Stay in Hospital for Suspected Community-Acquired Pneumonia - Jane Q Huang; Peter M Hooper; Thomas J Marrie (Canadian Respiratory Journal)
OBJECTIVE: To determine factors associated with the length of stay (LOS) for patients with suspected community-acquired pneumonia (CAP) who required hospitalization for treatment.